2016
DOI: 10.1108/ilt-05-2015-0063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface texturing on the tribological behavior of piston rings under lubricated conditions

Abstract: Purpose – The piston ring-cylinder liner pair is one of the most important tribological systems of an internal combustion engine. The friction loss of the piston ring-cylinder liner pair accounts for the largest portion of total efficiency losses. Therefore, improving the tribological system design of the piston ring-cylinder liner pair can reduce friction losses and bring tremendous economic benefits to society. This paper aims use surface texturing, which is proving to be an effective method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…A great deal of research has been done to study the effect of surface texturing on tribological properties of material (Kang et al , 2015; Xing et al , 2013; Dawit Zenebe Segu, 2016; Zhang et al , 2016). The results show that the shape, area density and distribution of surface texturing have a great effect on the tribological properties of material.…”
Section: Resultsmentioning
confidence: 99%
“…A great deal of research has been done to study the effect of surface texturing on tribological properties of material (Kang et al , 2015; Xing et al , 2013; Dawit Zenebe Segu, 2016; Zhang et al , 2016). The results show that the shape, area density and distribution of surface texturing have a great effect on the tribological properties of material.…”
Section: Resultsmentioning
confidence: 99%
“…Kligerman et al [25] developed an analytical model to evaluate the optimum dimple parameters such as dimple depth, texture area density, and textured portion of the nominal contact surface of a piston ring. Shen and Khonsari [26] and Zhang et al [27] conducted the experiments and discovered that (i) the friction performance of the ring surface improved significantly via surface texturing, (ii) the running-in duration shortened, and (iii) the sealing performance improved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, these tiny features also act as pits for wear debris and provide additional lubricant supply under starved lubrication conditions (Gachot et al , 2017). In the past two decades, numerous studies have been undertaken to explore the usefulness of surface texturing gas seals (Kligerman and Etsion, 2001), flat land thrust bearing (Brizmer et al , 2003), piston rings (Zhang et al , 2016), etc. These studies reported a significant enhancement in load supporting capacity and reduction in friction coefficient between the sliding surfaces.…”
Section: Introductionmentioning
confidence: 99%